O efeito do treinamento resistido associado ao consumo whey proteins e uso de decanoato de nandrolona sobre o índice de hipertrofia cardíaca de ratos wistar - SANTOS NETO, Ernani Eugênio dos (2022)
Introduction: Resistance is characterized by an effort made against an external and opposing force against a specific resistance produced, indicated for health promotion and prevention of cardiovascular diseases. When associated with protein supplementation, it also increases muscle mass and muscle strength. These incessant search for improvements in their body aesthetics, in addition to consuming supplements without guidance, questionable methods and without information, which are like applications of anabolic androgenic steroids. The misuse of this substance can occur in all categories of sport. its use has associations with cardiac pathologies, cardiac hypertrophy and even fatal cardiac events. Objective: To evaluate the cardiac hypertrophy index of male Wistar rats after twelve weeks of resistance training, supplemented with whey proteins and inoculated with nandrolone decanoate. Methods: This is an experimental research carried out at the Laboratory of Exercise Physiology and Prescription of Maranhão. 4 male rats were used with 2 groups divided into 03, containing eight animals in each group: Whey Decanoate (W2D), Decanoate Training (TD) and Whey Decanoate Training (TW2D). Rats remain on a 12-hour light dark lighting cycle fed with food and water ad Libidum. The animals were offered resistance training three times a week, with supplementation and inoculation of nandrolone decanoate once a week. After euthanasia, the heart was weighed and the cardiac hypertrophy index (HCI) was evaluated, which was calculated as the ratio between heart mass (mg) and body mass (g). Results: After 12 weeks of protocol, the animals showed an increase in body mass at baseline (p<0.0001). In the water intake there was a higher consumption in the W2D group in relation to the TW2D (p>0.0029). There was a higher feed intake in the TD group compared to W2D (p>0.0001) and TW2D (p>0.0001). When assessing cardiac mass, there was no significant difference between the groups (p<0.05). When analyzing the cardiac hypertrophy index, there was no significant difference between the groups (p<0.05). Discussion: The final body mass study has no significant difference, between the two groups that control only with other studies and two groups that control a body mass only with other studies, but with the role when starting an initial study with other studies , and but when starting a body mass study with other studies only, and but when starting a body mass study. combined training with nandrolone had a positive exercise deterrent on body mass and was associated with a lower gain. Cardiac mass did not present a significant difference between the studies and the one related to others, this statement was confirmed. The IHC was significantly among the other studies of group studies, but in contrast, that had differences in outcome with outcome differences compared to groups with no substance use differences. Conclusion: Resistance training associated with the ingestion of wh proteins and inoculation according to nandrol was not developed in cardiac mass gains or increases in IHC in male rats.